2018
DOI: 10.3390/f9070405
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Physical Properties of Conifer Cones with Relevance to Energy Production Efficiency

Abstract: The paper presents gross and net calorific values, ash content, conversion factors, and bulk density for different-sized spent cones of Scots pine Pinus sylvestris L., Norway spruce Picea abies L., European larch Larix decidua Mill., and Silver fir Abies alba Mill. harvested from various sites. Gross and net calorific value and bulk density were measured in accordance with the relevant EN and ISO standards. The density conversion factors were determined based on free space measurement by means of water immersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
(28 reference statements)
1
12
0
1
Order By: Relevance
“…Scots pine, Norway spruce, and European larch are the most widespread conifers in Europe used for seed harvesting. Aniszewska et al [ 29 ] have reported that spent conifer cones (after seed extraction) have a high energy potential and that as much as 0.6–1.2 million tons of cones could be obtained annually in Poland. Harvesting such an amount might require high costs; however, tree cones as a by-product are also generated in seed extraction facilities, which in Poland, produce on average several tens of tons of dry processed cones annually.…”
Section: Introductionmentioning
confidence: 99%
“…Scots pine, Norway spruce, and European larch are the most widespread conifers in Europe used for seed harvesting. Aniszewska et al [ 29 ] have reported that spent conifer cones (after seed extraction) have a high energy potential and that as much as 0.6–1.2 million tons of cones could be obtained annually in Poland. Harvesting such an amount might require high costs; however, tree cones as a by-product are also generated in seed extraction facilities, which in Poland, produce on average several tens of tons of dry processed cones annually.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are numerous reports concerning biomass of various origins that is produced for energy (i.e. "energy biomass") (Aniszewska et al 2018), its parameters, chemical composition, processing (Väisänen 2016), including processing into improved solid fuels (Gendek et al 2018b), and supply chain optimization (Dessbesell et al 2016). Miranda et al (2009) has determined the chemical composition and gross calorific value of pellets made of residues from Pyrenean oak.…”
Section: Introductionmentioning
confidence: 99%
“…The highest values were accumulated in the bark of larch and in needles of spruce, fir, and pine. Published calorific values for spruce biomass fractions are as follows (MJ kg 19.525-19.763. The differences in the calorific values between different parts of the tree can be greater than the differences between species.…”
Section: Discussionmentioning
confidence: 99%
“…Partial data can also be found for the calorific value of individual biomass fractions. Data have been published on the calorific values of the stem wood, branches, and roots of the bark of spruce and beech trees [18], the calorific value of wood and cones of four coniferous trees [19], as well as on the relationship of the calorific value of fir wood and the width of the annual rings [20]. A very detailed study of the heating values of seven tree species was conducted in Finland [21].…”
Section: Introductionmentioning
confidence: 99%